In vivo detection of RNA-binding protein interactions with cognate RNA sequences by fluorescence resonance energy transfer - Huranová, Martina; Jablonski, Joseph A; Benda, Ales; Hof, Martin; Stanek, David; Caputi, Massimo (RNA (New York, N.Y.), 2009)
Expression of the nascent RNA transcript is regulated by its interaction with a number of proteins. The misregulation of such interactions can often result in impaired cellular functions that can lead to cancer and a number of diseases. Thus, our understanding of RNA-protein interactions within the cellular context is essential for the development of novel diagnostic and therapeutic tools. While there are many in vitro methods that analyze RNA-protein interactions in vivo approaches are scarce. Here we established a method based on fluorescence resonance energy transfer (FRET), which we term RNA-binding mediated FRET (RB-FRET), which determines RNA-protein interaction inside cells and tested it on hnRNP H protein binding to its cognate RNA. Using two different approaches, we provide evidence that RB-FRET is sensitive enough to detect specific RNA-protein interactions in the cell, providing a powerful tool to study spatial and temporal localization of specific RNA-protein complexes.
Keywords: proteiny vázající RNA; Humans; HeLa buňky; sekvence nukleotidů; genetické vektory; RNA; Substrate Specificity; Protein Binding; vazebná místa; lidé; Binding Sites; rezonanční přenos fluorescenční energie; Base Sequence; HeLa Cells; substrátová specifita; vazba proteinů; Genetic Vectors; Fluorescence Resonance Energy Transfer; RNA-Binding Proteins